Different BAG-1 isoforms have distinct functions in modulating chemotherapeutic-induced apoptosis in breast cancer cells - Liu Hong-yu; Wang Zhuo-min; Bai Yun; Wang Min; Li Ying; Wei Sen; Zhou Qing-hua (Acta Pharmacologica Sinica, 2016)
Aim: BAG-1 is a multifunctional anti-apoptotic gene with four isoforms, and different BAG-1 isoforms have different antiapoptotic functions. In this study, we transfected BAG-1 isoforms into the human breast cancer cell lines Hs578T (ER negative) and MCF-7 (ER positive) to study their effect on apoptosis with or without estrogens. Methods: The constructed recombinant expression vectors carrying individual BAG-1 isoforms was used to transfect human breast cancer cell lines Hs578T (ER negative) and MCF-7 (ER positive). After stable cell lines were made, a variety of apoptosis-inducing agents, including doxorubicin, docetaxel, and 5-FU, was used to treat these cell lines with or without estrogen to test the role of BAG-1. The mechanism by which BAG-1 affected the function of Bcl-2 was exploredby using the cycloheximide chase assay. Results: The BAG-1 p50 and p46 isoforms significantly enhanced the resistance to apoptosis in both cell lines according to flow cytometry analysis. BAG-1 p33 and p29 failed to protect the transfected cells from apoptosis. The cell viability assay showed that only BAG-1 p50, but not p46, p33, or p29, increased estrogen-dependent function in ER-positive cell line MCF-7. Only BAG-1 p50 dramatically increased its anti-apoptotic ability in the presence of estrogen, while estrogen has very little effect on the anti-apoptotic ability of other BAG-1 isoforms. In the detection of the expression of K-ras, Hsp70, cytochrome c, Raf-1, ER-α, and Bcl-2 in MCF-7 cells by Western blot, only Bcl-2 protein expression was significantly increased in MCF-7 cells transfected with BAG-1 p50 and p46, respectively. Furthermore, the cycloheximide chase assay indicated that the degradation of Bcl-2 protein was extended in the BAG-1 p50 and p46 transfected MCF-7 cells. Conclusion: Distinct isoforms of BAG-1 have different anti-apoptotic functions in breast cancer cells, and that the BAG-1 p50 isoform can potentiate the role of estrogen in ER-positive breast cancer.